2011
DOI: 10.1017/s0003055411000165
|View full text |Cite
|
Sign up to set email alerts
|

Elite Influence on Public Opinion in an Informed Electorate

Abstract: A n enduring concern about democracies is that citizens conform too readily to the policy views of elites in their own parties, even to the point of ignoring other information about the policies in question. This article presents two experiments that undermine this concern, at least under one important condition. People rarely possess even a modicum of information about policies; but when they do, their attitudes seem to be affected at least as much by that information as by cues from party elites. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
465
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 536 publications
(504 citation statements)
references
References 57 publications
(135 reference statements)
33
465
4
2
Order By: Relevance
“…The notion that such position adoption can describe public opinion even some of the time has been understandably controversial (for a review, see Bullock 2011), but it is consistent with a number of broader theories. On the one hand, democratic theory suggests citizens may believe elites have superior policy information, expertise, or judgment (Burke 1774; see also Bianco 1994;Fox and Shotts 2009).…”
mentioning
confidence: 80%
“…The notion that such position adoption can describe public opinion even some of the time has been understandably controversial (for a review, see Bullock 2011), but it is consistent with a number of broader theories. On the one hand, democratic theory suggests citizens may believe elites have superior policy information, expertise, or judgment (Burke 1774; see also Bianco 1994;Fox and Shotts 2009).…”
mentioning
confidence: 80%
“…In recent decades, political scientists have put the second claim to test and found significant partisan bias in both factual and normative matters (for overviews, ! 10 see Bullock, 2011;Leeper & Slothuus, 2014). In particular, both observational and experimental studies have shown that supporters of a party support new policies from that party somewhat independently of content of those policies (e.g., Cohen, 2003;Rahn, 1993).…”
Section: The Psychology Of Politicsmentioning
confidence: 99%
“…Recent studies in the U.S. show that a voter's partisan biases affect their willingness to internalize new information (e.g. Jerit and Barabas 2012; Boudreau and MacKenzie 2014;Bullock 2011;Gerber and Huber 2010), while European studies have indicated that poorly informed voters are most sensitive to new information (e.g. Duch 2001).…”
Section: Voter Sophisticationmentioning
confidence: 99%